Gene-knockout mice in malaria research: Useful or misleading? - Hernández Valladares, M.; Naessens, Jan; Iraqi, F.A. (Elsevier, 2007)
Gene-knockout mice have been extensively used in the study of several malaria-induced pathologies. Some investigators believe that the deficient, infected mice mimic disease aspects produced in the absence of the target gene, but others believe that the deficient mice models mainly explain the effects of compensatory, related molecules. Comparison of some of the most relevant knockout mouse studies for understanding cerebral malaria and parasitemia and their related human reports shows that gene-knockout mice are useful tools that support conclusions from human genetic studies. These mice have helped to indicate new resistance genes against human malaria and have provided valuable information about mechanisms of malaria resistance in mice.